The Importance of Change Management in Educational Institutions - Nisak, Hernik Khoirun (STAI MA'ARIF MAGETAN, INDONESIA, 2023)
Management as a science that was only recognized in the mid-19th century, management is known as the key to the success and success of managers of companies or educational institutions, both public educational institutions and Islamic educational institutions. There are even people who consider management of Islamic education as a